Hubungan Dukungan Keluarga dengan Harga Diri Pada Pasien Kusta di Klinik Kulit dan Kelamin RSUD dr. Saiful Anwar Malang - Suhermin, Yayuk (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Leprosy is a skin disease caused by the leprosy germ (Mycobacterium leprae) that can have physicaland psychological impacts. This can be an obstacle for a leprosy patient to carry out their daily activities. Therefore, family support is needed to increase the selfesteem of leprosy patients, so that a leprosy patient hasthe ability to live hislife. The purpose of this study was to determine the relationship of family support to patient self-esteem at the skin and genital clinic of Dr. Saiful Anwar Hospital Malang. This study used observational analytic research using a cross sectional study design. The population was all patients diagnosed with leprosy. The sampling technique used in thisstudy was purposive side, the sample size was 43 patients, data collection was carried out by distributing questionnaires for 3 months, from June to August 2023, hypothesis testing using Spearman's rho test with = 0.05. Family support is one of the efforts to improve the coping strategies of leprosy patients because with family support, leprosy patients will feel valued, loved and part of the family.